Determinants of Career Choices among Management Students under Tribhuvan University in Nepal - Thapa, Bhim Kumar (International Research Journal of MMC, 2023)
This research investigates the challenges of career decision making among management students at Tribhuvan University in Nepal, utilizing a quantitative approach through a questionnaire survey. The study aims to comprehensively assess the impact of key variables: Interest in the Subject, Ease of Subject, Financial Outcomes, Future Job Opportunities and Interpersonal Influences on students' career choices. Employing a multiple linear regression model, the analysis indicates a reliable relationship between these independent variables and the dependent variable Career Choice with a substantial coefficient of determination (R Square = 0.782) and adjusted R Square (0.773). Particularly remarkable are the significant roles of Financial Outcomes and Future Job Opportunities as predictors (p < 0.001), indicating their considerable influence on career decisions. Interest in the Subject, Ease of Subject, and Interpersonal Influences display non-significant coefficients, suggesting limited impact within this student group. These findings hold significant implications for educational institutions and policymakers, emphasizing the importance of incorporating practical exposure and information related to financial aspects and job prospects in curriculum design and career counseling services.